Soil Compactability - Seig, D. A. (Cranfield University, 1985)
Subsoiling and deep loosening are widely used to alleviate soil compaction but little is known about the mechanics of the compaction process. Further information is required on the process that soil goes through during compaction, along with the effect on the amount of soil compaction of various tyre configurations. Such information will allow more confident recommendations to farmers on the suceptability of their soil to compaction. Experimental work was conducted where the soil deformtions of a light textured soil were monitored throughout the whole soil mass. The deformations in the soil were caused by a loaded pneumtic tyre on the surface. In the experimental work, both the process of soil compaction and the final state of the soil following the passage of a wheel were monitored. The experiments showed that soil compaction on light textured soils is caused by a punch failure of the soil, therefore most of the compaction is confined to the area directly below the wheel. The experimental monitoring of soil deformations was a slow and complex process, drawing firm conclusions from the work was further complicated by the interactions of the input variables, such as load and contact length. In order to monitor the effect of individual inputs on soil compaction a thre dimensional mathematical model of the process was developed from Theories of Elasticity and a confined compression soil test. The model predicted the subsurface deformations in the three principle directions due to surface loads. Once the model was modified to account for the support capability of the soil it proved it could, with resonable accuracy, predict the defomations and hence soil canpaction due to a tyre on the soil surface. The model was used to predict the effect of various tyre configurations on soil ccrnpaction. From a number of these runs it was possible to find the sensitivity of soil to compaction due to that input. The results showed that the sensitivity of soil to ccmpaction is not a linear relationship and significant reductions in the amount of soil, canpacted and the level of ihe compaction can be achieved by the right tyre configuration.